2010
DOI: 10.1038/msb.2010.3
|View full text |Cite
|
Sign up to set email alerts
|

Revealing a signaling role of phytosphingosine‐1‐phosphate in yeast

Abstract: Perturbing metabolic systems of bioactive sphingolipids with genetic approachMultiple types of “omics” data collected from the systemSystems approach for integrating multiple “omics” informationPredicting signal transduction information flow: lipid; TF activation; gene expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 39 publications
0
44
1
Order By: Relevance
“…Moreover, it is expected that bioinformatic approaches will also help in the quest to define lipid-specific functions. In such an approach, functions for yeast sphingoid base phosphates were elucidated by "deconvoluting" gene-based transcriptomic data to lipidbased regulation by simultaneously analyzing transcriptomic and lipidomic results (95). Another very recent approach helps visualize sphingolipidomic results and correlates those with functional changes in transcriptomic data on sphingolipid enzymes (96).…”
Section: Implications Of This Paradigm Shiftmentioning
confidence: 99%
“…Moreover, it is expected that bioinformatic approaches will also help in the quest to define lipid-specific functions. In such an approach, functions for yeast sphingoid base phosphates were elucidated by "deconvoluting" gene-based transcriptomic data to lipidbased regulation by simultaneously analyzing transcriptomic and lipidomic results (95). Another very recent approach helps visualize sphingolipidomic results and correlates those with functional changes in transcriptomic data on sphingolipid enzymes (96).…”
Section: Implications Of This Paradigm Shiftmentioning
confidence: 99%
“…Recently, intracellular functions of sphingosine 1 phosphate in vertebrates have been revealed in control of protein ubiquitination (Alvarez et al 2010) and transcription (Hait et al 2009). In yeast, recent studies integrating genomic, transcriptomic, and lipidomic data have revealed a role for phytosphinganine 1 phosphate in regulating genes involved in mitochondrial respiration (Cowart et al 2010). Another sphingolipid connection to mitochondrial function comes from the dual localization of the yeast sphingomyelinase homolog, Isc1p, which is found in both ER and mitochondria (Vaena de Avalos et al 2004).…”
Section: Genetic Approaches To Sterol and Sphingolipid Functionmentioning
confidence: 99%
“…For the GPI-anchored proteins this could be because of the fact that most GPI-anchored proteins are remodeled to contain ceramide (Reggiori et al 1997) and that this step is required for their concentration into ER exit sites ). Sphingolipids also play roles in regulation of translation affecting formation of RNA processing bodies (Cowart et al 2010) and regulating translation initiation during the heat shock response (Meier et al 2006).…”
Section: Genetic Approaches To Sterol and Sphingolipid Functionmentioning
confidence: 99%
“…The lcb4⌬,lcb5⌬ double deletion strain, deleted in both sphingoid base kinases LCB4 and LCB5, showed up-regulation that was not significantly different from wild type, implying that the sphingoid base phosphates are not required for mediating CHA1 expression. This is a relevant conclusion because previous work has implicated PHS-1-phosphate in up-regulation of specific genes during heat stress (4,22,23) and therefore distinguishes DHS/PHS versus PHS-1-phosphate-regulated pathways. The lag1⌬ and lac1⌬ strains deleted in the ceramide synthases showed normal up-regulation, disfavoring the possibility that ceramide synthesis is required for CHA1 up-regulation.…”
mentioning
confidence: 68%
“…In particular, several responses to heat stress have been shown to require de novo synthesis of sphingolipids, and these include cell cycle arrest, proteolysis, and nutrient import (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%